The The Role of Information Media in the Utilization of Rice Field Technology in Galung Village, Lilirilau District, Soppeng Regency - La Sumange La Sumange; Muhammad Asir; Syamsul Rahman; Mufidah Muis; St. Aisyah R (Jurnal Agrisistem: Seri Sosek dan Penyuluhan, 2026)
The utilization of Internet- and multimedia-based information technology has become increasingly important in supporting the productivity enhancement of rice farming as part of strengthening contemporary food security. This shift reflects a transition from conventional agricultural practices toward farming that is more adaptive to technological developments, particularly among millennial farmers.  This study aims to examine the role of information media in the adoption of rice farming technology. The research was conducted in Galung Subdistrict, Liliriaja District, Soppeng Regency, South Sulawesi Province, during the period of February to April 2025. The study population consisted of 153 rice farmers, from which a sample of 15% was determined, resulting in 23 respondents. Data were analyzed using descriptive methods with a Likert scale.  The results indicate that social media plays a crucial role in expanding the dissemination of agricultural information while simultaneously encouraging technology adoption at the farmer level. Among the platforms used, YouTube had the strongest influence, with scores ranging from 2.9 to 3.7. Facebook followed with scores between 2.1 and 3.6, while WhatsApp scored between 1.3 and 2.8. These differences reflect variations in the effectiveness of each medium according to platform characteristics and the quality of the content presented. This research finding indicates that the integration of social media with field extension conducted every three months can enhance understanding, acceptance, and adoption of various agricultural technologies, as reflected in farmers’ active engagement in technology usage practices and interactions through social media.